Effect of Methane on Combustion of Glycerol and Methanol Blends Using a Novel Swirl Burst Injector in a Model Dual-Fuel Gas Turbine Combustor - S. M. Rafiul Islam; Ishaan Patel; Lulin Jiang (Clean Technologies)
Glycerol, a byproduct of biodiesel, has moderate energy but high viscosity, making clean combustion challenging. Quickly evaporating fine fuel sprays mix well with air and burn cleanly and efficiently. Unlike conventional air-blast atomizers discharging a jet core/film, a newly developed swirl burst (SB) injector generates fine sprays at the injector’s immediate exit, even for high-viscosity fuels, without preheating, using a unique two-phase atomization mechanism. It thus resulted in ultra-clean combustion for glycerol/methanol (G/M) blends, with complete combustion for G/M of 50/50 ratios by heat release rate (HRR). Lower combustion efficiencies were observed for G/M 60/40 and 70/30, representing crude glycerol. Hence, this study investigates the effect of premixed methane amount from 0–3 kW, and the effect of atomizing gas to liquid mass ratio (ALR) on the dual-fuel combustion efficiency of G/M 60/40-methane in a 7-kW lab-scale swirl-stabilized gas turbine combustor to facilitate crude glycerol use. Results show that more methane and increased ALR cause varying flame lift-off height, length, and gas product temperature. Regardless, mainly lean-premixed combustion, near-zero CO and NOx emissions (≤2 ppm), and ~100% combustion efficiency are enabled for all the cases by SB atomization with the assistance of a small amount of methane.